2015
DOI: 10.1016/j.crad.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Ex-PRESS glaucoma filter: an MRI compatible metallic orbital foreign body imaged at 1.5 and 3T

Abstract: AIM To report on the MRI compatibility of the Ex-PRESS glaucoma filtration device, a tiny metallic implant placed into the anterior chamber of the eye that is much smaller than traditional glaucoma shunts, and to educate the radiology community regarding its appearance. MATERIALS AND METHODS Seven patients with Ex-PRESS glaucoma filtration devices were identified that had undergone MRI at San Francisco General Hospital/University of California San Francisco Medical Center by searching and cross-referencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Geffen et al [6] studied the influence of a magnetic field 1.5 and 3 T on an EX-PRESS implant under various conditions, including human eyes (post mortem), and came to the conclusion that undergoing MR with an implanted EX-PRE-SS implant up to 3 T is safe as a result of the ocular tissue which prevents the movement of the device. Seibold et al [17] examined the movement of an EX-PRESS implant in various magnetic fields, and also determined that the implant is safe for MR of as much as 3 T. Mabray et al [10] also demonstrated that the presence of an EX-PRESS implant in the eyes of patients did not cause any significant artefacts influencing the diagnostic interpretation of their MR. In our study none of the patients has yet had do undergo MR examination.…”
Section: Discussionmentioning
confidence: 99%
“…Geffen et al [6] studied the influence of a magnetic field 1.5 and 3 T on an EX-PRESS implant under various conditions, including human eyes (post mortem), and came to the conclusion that undergoing MR with an implanted EX-PRE-SS implant up to 3 T is safe as a result of the ocular tissue which prevents the movement of the device. Seibold et al [17] examined the movement of an EX-PRESS implant in various magnetic fields, and also determined that the implant is safe for MR of as much as 3 T. Mabray et al [10] also demonstrated that the presence of an EX-PRESS implant in the eyes of patients did not cause any significant artefacts influencing the diagnostic interpretation of their MR. In our study none of the patients has yet had do undergo MR examination.…”
Section: Discussionmentioning
confidence: 99%
“…A small consecutive case series by De Feo et al 25 found that the implant caused minimal artifacts on MRI of the orbit and brain, although the imaging quality of the optic nerve itself may have been slightly decreased. Mabray et al 26 confirmed in their small retrospective study that the presence of an EX-PRESS in patient eyes did not cause any significant artifacts affecting the diagnostic interpretation of their MRI scans.…”
Section: Comparison Of Ex-press With Trabeculectomymentioning
confidence: 85%
“…1 Even though it is influenced by magnetic field forces, magnetic resonance imaging (MRI) is considered safe in patients with EX-PRESS shunt. 2,3 We present a case of late-onset spontaneous EX-PRESS dislocation into the anterior chamber, coincidentally after a positron emission tomographyÀcomputed tomography (PET-CT) scan.…”
Section: Late-onset Spontaneous Ex-press Shunt Dislocation Into Anterior Chambermentioning
confidence: 99%
“…There are no absolute contraindications for a PET scan because only small amounts of radiation are given, in fact less than those given for a diagnostic CT scan. 3 In general, patients with metallic implants, pacemakers, prostheses, or other devices can safely undergo a whole-body PET scan. The only adverse effect of metallic devices is that they can cause fluorodeoxyglucose uptake around them, and this could simulate inflammation.…”
Section: Late-onset Spontaneous Ex-press Shunt Dislocation Into Anterior Chambermentioning
confidence: 99%